An Innovative Fintech Model for The Enhancement of Akhuwat Microfinance Practices - Shahid, Mohammad; Khaliq, Ahmad; Mohtesham, Mohammed Meeran Jasir (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2021)
Abstract. To accelerate Akhuwat microfinance growth and lessen its cost to assist the poor, the current study proposes Fintech Rich Hybrid Islamic Micro-Finance (FRHIMF) model. This study adopts a qualitative approach relying on the content analysis of secondary sources, such as research articles, journals, conference papers, and websites. The study reveals that to achieve socio-economic mobility, poor people are in requisite of adequate financing. However, Islamic commercial banks generally finance major businesses and medium- to high-income proficient workers in consumer finance. Thus, the poor are unable to access funding to meet their liquidity constraints and the needs of small business finance. Akhuwat microfinance is a globally renowned institution that has played a vital role in supporting the underprivileged community. The implementation of FRHIMF has greater potential to increase Akhuwat microfinance accessibility.Keywords. Microfinance, Akhuwat, Poverty, Fintech Rich Hybrid Islamic Micro-FinanceJEL: D64,O1,O2 Abstrak. Untuk mempercepat pertumbuhan keuangan mikro Akhuwat dan menekan biayanya untuk membantu orang miskin, studi ini mengusulkan model Fintech Rich Hybrid Islamic Micro-Finance (FRHIMF). Studi ini mengadopsi pendekatan kualitatif dengan melakukan analisis konten terhadap sumber-sumber sekunder berupa hasil-hasil penelitian, jurnal, makalah konferensi, dan situs web. Kajian ini mengungkapkan bahwa untuk mencapai mobilitas sosial ekonomi, masyarakat miskin membutuhkan pembiayaan yang memadai. Namun, bank syariah umumnya membiayai bisnis besar dan pekerja terampil berpenghasilan menengah ke atas untuk pembiayaan konsumsi. Dengan demikian, masyarakat miskin tidak dapat mengakses pendanaan untuk memenuhi kendala likuiditas dan kebutuhan pembiayaan usaha kecil. Keuangan mikro Akhuwat adalah lembaga yang terkenal secara global yang telah memainkan peran penting dalam mendukung masyarakat yang kurang mampu. Penerapan FRHIMF berpotensi besar untuk meningkatkan aksesibilitas keuangan mikro Akhuwat.Kata kunci. Keuangan Mikro, Akhuwat, Kemiskinan, Fintech Rich Hybrid Islamic Micro-FinanceJEL: D64,O1,O2